Contribution of predation to the biological control of a key herbivorous pest in citrus agroecosystems - Bouvet, Juan Pedro (2019)
Biological control has traditionally simplified the view of trophic relationships between herbivorous pests and their natural enemies in agriculture. The success or failure of this pest management strategy is still mainly attributed to the ability of a few key natural enemies to suppress the pest density. For example, successful regulation of the California red scale (Aonidiella aurantii), a key citrus pest, is generally credited to specific parasitoids of the Aphytis genus. Currently, research is revealing how herbivore regulation in agroecosystems can be alternatively achieved with a greater number of trophic associations within the system. The goals of the present study were as follows: i) to unravel species‐specific trophic links between A. aurantii and its natural enemies in citrus agroecosystems, and ii) to assess their contribution to control of A. aurantii. Predation and parasitism of this herbivorous pest were assessed through exclusion experiments. Species‐specific trophic links between this herbivorous pest and its natural enemies were studied using gut‐content analysis of field‐collected predators employing prey‐specific DNA molecular markers. Relative predation rates of the species involved in A. aurantii regulation were estimated. Predation was found to be the main biotic component of A. aurantii mortality, causing reductions of more than 75% in recently settled cohorts. Aonidiella aurantii DNA was detected in the digestive system of 11 species of predators. Generalist and stenophagous predators, mainly associated with other citrus pests such as aphids, proved to be the most important biological control agents of this pest. Complex trophic relationships, such as apparent competition between two key citrus pests, were revealed. The present study highlights the role of predation as biotic mortality factor of key pests in perennial agroecosystems, wherein it is a rich complex of indigenous or naturalized generalist predators that are primarily responsible for this mortality. The results herein presented may therefore offer another perspective on the biological control of one of the key world‐wide citrus pests, at least in those regions where specific parasitoids are not able to successfully regulate the scale populations.